Financial Structure and Corporate Growth: Evidence from Italian Panel Data. (5th May 2016) - Molinari, Massimo; Giannangeli, Silvia; Fagiolo, Giorgio
Abstract : We study the relationships between firm financial structure and growth for a large sample of Italian firms (1998–2003). We expand upon existing analyses testing whether liquidity constraints affect firm expansion by considering amongst growth determinants also firm debt structure within a unified framework. Panel regression analyses show that more liquid firms tend to grow more. However, firms do not use their capital to expand, but rather to increase debt. We also find that firm growth is highly fragile as it is positively correlated with non‐financial liabilities and it is not sustained by a long‐term debt maturity. Finally, quantile regressions suggest that fast‐growing firms are characterized by higher growth/cash‐flow sensitivities and heavily rely on external debt, but seem to be less bank‐backed than the rest of the sample. Overall, our findings suggest that the link between firms' financial structure and expansion decisions is far more complicated than postulated by standard tests of investment/cash‐flow sensitivities.